Estimation of the diagnostic accuracy of the glyco-C and US9 gene-based polymerase chain reaction technique for the detection of bovine Herpesvirus type 5 DNA in decomposed brain suspension from a slaughter house using Bayesian analysis, Brazil - Cardoso, Tereza Cristina [UNESP]; Antello, Talita Fontes [UNESP]; Vieira, Flávia Volpato [UNESP]; Machado, Saulo Tarso Zacarias [UNESP]; Nogueira, Adriana Hellmeister de Campos (Springer Nature, 2012)
Brazil represents the greatest beef producer among tropical countries, and the major obstacle for meat international trade is sanitary problems especially closely related to viral encephalitis. The goal of this study was to estimate the accuracy of the glycol and US9 gene-based polymerase chain reactions (PCRs) for the detection of bovine Herpesvirus type 5 (BoHV-5) from decomposed brain samples (n = 95). For this purpose, a latent-class (bayesian) approach was used. Sensitivity (Se) was estimated to be 70% (95% probability interval, 40-80) and specificity (Sp) 100% in the statistical analysis for both PCRs used. Accordingly, a minimum of ≥40% of the calves was estimated to harbor BoHV-5 DNA even after 72 h of decomposition at room temperature. It was concluded that US9 gene-based PCR could also be considered a cost-effective alternative in sanitary programmers. However, given the importance of veterinary diagnoses, PCR-positive samples should be further confirmed through in vitro isolation and/or sequencing.
Keywords: Bovine Herpesvirus type 5; Gold standard; Diagnosis